Proceedings of the 7th ACM Workshop on Performance Monitoring and Measurement of Heterogeneous Wireless and Wired Networks 2012
DOI: 10.1145/2387191.2387206
|View full text |Cite
|
Sign up to set email alerts
|

Analytic comparison of wake-up receivers for WSNs and benefits over the wake-on radio scheme

Abstract: Since in most wireless sensor network (WSN) scenarios nodes must operate autonomously for months or years, power management of the radio (usually consuming the largest amount of node's energy) is crucial. In particular, reducing the power consumption during listening plays a fundamental role in the whole energy balance of a sensor node, since shutting down the receiver when no messages are expected can remarkably increase the autonomy. Idle listening is a hard challenge because incoming messages are often unpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(62 citation statements)
references
References 24 publications
(49 reference statements)
0
62
0
Order By: Relevance
“…Among the different categories of duty-cycling, namely synchronous, pseudo-asynchronous and pure asynchronous. The latter provides the most efficient solution in terms of energy consumption [3].…”
Section: B Wake-up Radio Schemementioning
confidence: 99%
See 1 more Smart Citation
“…Among the different categories of duty-cycling, namely synchronous, pseudo-asynchronous and pure asynchronous. The latter provides the most efficient solution in terms of energy consumption [3].…”
Section: B Wake-up Radio Schemementioning
confidence: 99%
“…Although there are numerous methods to achieve energy efficiency, such as using lightweight communication protocols [2] or adopting low-power radio transceivers [3], the recent technology trend in energy harvesting provides a fundamental method to prolong battery longevity. Thus, energy harvesting is a promising approach for the emerging IoT [4].…”
Section: Introductionmentioning
confidence: 99%
“…Note that several studies such as Ref. [15] reported that the idle listening consumes significant power and is a major factor to reduce network lifetime. Their idea in Ref.…”
Section: Related Workmentioning
confidence: 99%
“…The other is asynchronous wake-up by external triggers. In this method, each node uses a low power wake-up radio (WuR) [4][5][6] to accept remote wake-up request, and activates its powerhungry parts on demand. Recently, the standardization of wake-up control for WLAN module was started as well [7].…”
Section: Introductionmentioning
confidence: 99%